The Relevance of FoMO Phenomenon in the Digital Age to the Concept of Zuyyina in the Qur'an: An Integrative Semantic Analysis from the Perspective of Self-Determination Theory - Muhammad Arsyad; Bashori (Journal of Islamic Thought and Contemporary Studies, 2025)
Fear of Missing Out (FoMO) is a contemporary psychological phenomenon characterized by pervasive anxiety that others are having rewarding experiences that one does not possess. This phenomenon shows similarities with the concept of zuyyina in the Qur'an, which describes psychological mechanisms where worldly objects appear more attractive than their actual reality. This study aims to analyze the relevance between FoMO and the zuyyina concept through Self-Determination Theory (SDT) perspective and explore practical implications for developing integrative interventions. The research employs a qualitative approach with semantic and comparative analysis, integrating in-depth analysis of the zuyyina concept with empirical findings on FoMO from contemporary psychological research. Results reveal significant convergence between zuyyina and FoMO in four main dimensions: attraction to external stimuli, social comparison dynamics, impact on attention and priorities, and affective anxiety components. SDT proves to be an effective theoretical framework for understanding how both phenomena interact with basic human psychological needs. This research contributes to developing an interdisciplinary analytical framework and opens opportunities for developing integrative interventions that combine traditional spiritual insights with contemporary psychology to address digital era mental health challenges.